Avaliação de metodologias de levantamentos planialtimétrico para elaboração de projeto de regularização fundiária - Silva Júnior, Francisco Nélio da (Universidade Federal Rural do Semi-Árido, 2020)
The accelerated process of urban growth that occurred in Brazil during the 1950s, in parallel with the increase in social inequality, together with the lack of public policies capable of supporting population growth, end up generating, in addition to the current housing problem, the multiplication of slums, among other irregular occupation modes, in Brazilian urban centers. In this context, Urban Land Regularization aims to guarantee the fundamental rights of citizens to live with dignity, the right to housing and the fulfillment of the social function of housing. As one of the essential parts of the REURB process is the land regularization project, which must contain the cadastral planialtimetric survey of the urban nucleus targeted for regularization. In view of the growing technological advancement in the survey methods employed, such as total stations, GNSS RTK and aerophotogrammetry using UAV. Therefore, this research aims to carry out an evaluation of planialtimetric survey methodologies, in view of the final product purchased, cost benefit and productivity. To carry out the analysis, an area of two blocks was chosen in the housing complex, where it was used to raise by irradiation using a total station, collecting points with GNSS RTK and aerophotogrammetry with UAV, the acquired data were processed and compared among themselves. Finally, showing that all methodologies are capable of being used in the land regularization project, their use together proving to be the most efficient.
Keywords: Cartografia; Aerofotogrametria; REURB; Cartography; Aerophotogrammetry; ENGENHARIAS::ENGENHARIA CIVIL